Tectonic Switch From Triassic Contraction to Jurassic-Cretaceous Extension in the Western Tarim Basin, Northwest China: New Insights Into the Evolution of the Paleo-Tethyan Orogenic Belt - Wu, Hongxiang; Cheng, Xiaogan; Chen, Hanlin; Chen, Cai; Dilek, Yildirim; Shi, Jun; Zeng, Changmin; Li, Chunyang; Zhang, Wei; Zhang, Yuqing; Lin, Xiubin; Zhang, Fengqi (Frontiers in Earth Science, 2021)
We use stratigraphic, sedimentological, and borehole data and seismic profiles from the western Tarim Basin to document its Mesozoic tectonic evolution. A nearly 60-km-wide, Triassic fold-and-thrust belt along the southwestern margin of Tarim Basin is unconformably overlain by a Jurassic-Cretaceous sedimentary sequence along a regional angular unconformity. The Lower-Middle Jurassic strata consist mainly of an upward-fining sequence ranging from terrestrial conglomerates to turbidite deposits, which represent the products of an initial rift stage. Palaeocurrent analyses show that sediments for these rift deposits were derived from the paleo-Kunlun and paleo-Tienshan Mountains to the southwest and northern, respectively. The overlying Upper Jurassic-Cretaceous series consist of coarse-grained, alluvial fan to braided river deposits in the lower stratigraphic member, and lagoonal mudstones and marine carbonates in the upper member. These finer-grained rocks were deposited in a subsiding basin, indicating that a significant change and reorientation in the drainage system should have occurred within the basin during the Early Cretaceous. The western Tarim Basin evolved from a syn-rift stage to a post-rift stage during the Jurassic-Cretaceous. A post-orogenic stretch developed due to the evolution of the Paleo-Tethyan orogenic belt in Central Asia is a likely geodynamic mechanism for this major tectonic switch from a contractional episode in the Triassic to an extensional deformation phase in the Jurassic-Cretaceous.